Comparative study of hsC-reactive protein nd lipid profiles of members of four Filipino families suspected with familial hypercholesterolemia - Paladar, Elde Mel B.
C-reactive protein and LDL-cholesterol have a strong linear relation with the incidence of cardiovascular disease (Ridker, 2002). However, Familial Hypercholesterolimia (FH) patient-based data directly comparing these two biologic markers are not available.In this study total cholesterol, HDL cholesterol (HDLc), LDL cholesterol (LDLc) and high sensitive C-reactive protein (hsCRP) profiles of members of four Filipino families suspected with FH and age-and gender-matched normal healthy individuals were measured and compared, in order to determine if lipid profile is directly related with hsCRP level in FH patients.The study initially surveyed some 32,800 patients from the blood chemistry records of the five cooperating hospitals. From these, 352 were found hypercholesterolimic based on their total cholesterol. From the 352, 60 individuals were suspected with FH based on high total cholesterol and LDL cholesterol, history of cardiovascular disease in the family, and normal blood sugar and creatinine. From the 60, 17 subjects belong to four (4) Filipino families. These 17 individuals composed the final population of this study. Seventeen normal, healthy Filipinos, age-and gender-matched of the 17 subjects suspected with FH were recruited to be normal control in the study.